Lactobacillus rhamnosus modulates murine neonatal gut microbiota and inflammation caused by pathogenic Escherichia coli - Xuan, Hao; Umar, Shahid; Zhong, Cuncong; Yu, Wei; Ahmed, Ishfaq; Wheatley, Joshua L.; Sampath, Venkatesh; Chavez-Bueno, Susana (BMC microbiology, 2024)
Background Pathogenic Escherichia coli strains produce neonatal septicemia after colonizing the neonatal gut. While the probiotic Lactobacillus rhamnosus GG (LGG) effectively reduces neonatal sepsis, LGG’s effects on the neonatal intestinal microbiota alterations and inflammation triggered by E. coli are incompletely understood. We hypothesized that LGG significantly modulates the specific neonatal gut microbial populations changes and the inflammatory response elicited by the enteral introduction of septicemia-producing E. coli . To test this hypothesis, newborn rats were pretreated orally with LGG or placebo prior to infection with the neonatal E. coli septicemia clinical isolate SCB34. Amplicon 16S rRNA gene sequencing was performed on intestinal samples. Intestinal injury and expression of inflammatory mediators and apoptosis were determined. Results Alpha diversity of gut microbiota was greater in SCB34-infected pups in comparison to sham-infected pups, these changes were not modified by LGG pretreatment. Beta diversity analyses also showed differences between SCB34-infected vs. uninfected pups. LGG pretreatment before SCB34 infection did not result in significant beta diversity changes compared to placebo. Moreover, individual genera and species abundance analyses by linear discriminant analysis effect size (LEfSe) showed significant changes in Gram-negative, Gram-positive, and anaerobic populations resulting from LGG pretreatment and SCB34 infection. LGG significantly suppressed the expression of inflammatory cytokines but did not attenuate SCB34-induced apoptosis or histologic injury. Conclusions LGG modulates clinically significant microbiota features and inflammation triggered by pathogenic E. coli intestinal infection shortly after birth. This new knowledge can potentially be harnessed to design novel interventions against gut-derived neonatal sepsis.